PENGARUH PEMANFAATAN PATI SANTAN KELAPA SEBAGAI MASKER RAMBUT (HAIR MASK) TERHADAP KELEMBABAN RAMBUT PASCA REBONDING - Karlina, Yana; Rahmiati, Rahmiati; Astuti, Murni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research uses quasi experimental quasi experimental method with design of Non Equivalent Control Group Design. The object of this study is dry hair due to rebonding. The population in this study is UNP students aged 18-25 years, have the same criteria. Sampling was taken by Purposive Sampling technique which was conducted by voolunteer (volunteer) with the number of samples of 9 people. The data collected from this research are primary data obtained directly from the sample. The collected research data was analyzed using descriptive analysis, and using Normality Test, Homogeneity Test, Variance Analysis Test (ANAVA) and DUNCAN Test. Based on the results of data, showed that in the control group (X0) without using coconut milk starch showed very dry conditions changed in dry conditions, and not yet in the Normal category or humid. In the experimental group 1 (X1) using coconut milk starch 1 times 2 days there were significant changes as well as in the experimental group 2 showing the results on hair moisture indicator. The hypothesis was accepted because < 0.050 and then continued with DUNCAN Test which showed significantly different groups.Keywords: Coconut milk Starch, Post Rebonding, Moisture Hair